TRADE OPENNESS AND INDUSTRIAL OUTPUT GROWTH IN NIGERIA: EMPIRICAL LESSONS FOR DIVERSIFICATION - MBA, Peter N.; ORJI, Anthony; CHUKWUMAEZE, Donald; ANTHONY-ORJI, Onyinye (Theoretical and Practical Research in Economic Fields; Vol 10 No 2 (2019): TPREF, Volume X, Issue 2(20), Winter 2019, 2019)
This study examines the relationship between trade openness and industrial output growth in Nigeria using time series data, endogenous growth framework as well as export-led growth model. The adopted framework contends that domestic policies on trade liberalization cannot be avoided but harnessed for optimal benefit of the economy. The empirical results show that trade openness contribute positively to industrial output growth and supports general economic diversification. In the short-run, the dynamic impact of trade openness on industrial output growth is insignificant while its long-run impact is significant.